Work-related stress in a humanitarian context: a qualitative investigation - Jachens, Liza; Houdmont, Jonathan; Thomas, Roslyn (Wiley, 2018)
There is a paucity of research into the subjective stress-related experiences of humanitarian aid workers (HAWs). Most studies investigating stress in HAWs focus on trauma and related conditions or adopt a quantitative approach. This interview-based study explored how HAWs (n=58) employed by a United Nations aligned organisation perceived the transactional stress process. Thematic analysis revealed eight main themes. An emergency culture was found where most employees felt compelled to offer an immediate response to humanitarian needs. Employees experienced a strong identification with humanitarian goals and reported high engagement. The rewards of humanitarian work were perceived as motivating and meaningful. Constant change and urgent demands resulted in work overload. Managing work-life boundaries and receiving positive support from colleagues and managers helped buffer perceived stress, work overload and negative health outcomes. The practical implications of the results are discussed and suggestions made in light of current research and stress theory.